Validity of a self‐administered diet history questionnaire for estimating vitamin D intakes of Japanese pregnant women - Shiraishi, Mie (Matern Child Nutr, 2013)
Maternal vitamin D status is important for fetal development and the prevention of pregnancy complications. Mothers require both sufficient intakes and skin production of this vitamin. We investigated the validity and test–retest reliability of a self‐administered diet history questionnaire (DHQ) to establish a method of assessing vitamin D intakes of Japanese pregnant women, using a serum marker. A total of 245 healthy pregnant women in the second trimester, who were not taking vitamin D supplements, were recruited at a university hospital in Tokyo between June 2010 and July 2011. Serum 25‐hydroxyvitamin D [25(OH)D] concentrations were measured as an indicator of vitamin D status. To assess the test–retest reliability of the DHQ, 58 pregnant women completed it twice within a 4–5‐week interval. Significant positive correlations between intakes and serum concentrations of vitamin D were found (r = 0.266 for daily intakes and r = 0.249 for energy‐adjusted intakes). In the winter investigation in which the serum 25(OH)D concentrations were less likely to be affected by sunlight exposure, the correlation coefficients were 0.304 for both daily and energy‐adjusted intakes. After excluding participants with pregnancy‐associated nausea, the coefficients increased. The intraclass correlation coefficient between vitamin D intakes estimated from the two‐time DHQ was 0.638. The DHQ provides an acceptable validity and reliability of the vitamin D intake of Japanese pregnant women. However, the data of women with nausea should be interpreted with caution. We believe that the DHQ is a useful questionnaire to grasp and improve vitamin D intakes during pregnancy.